The Effect of shoot density on growth, recruitment and reproduction of Enhalus acoroides (L.f.) Royle at Haad Chao Mai National Park, Trang Province, Thailand - Ekkalak Rattanachot (Prince of Songkla University, 2010)
Thesis (M.Sc., Ecology)--Prince of Songkla University, 2008